EXTENSIVE READING: WHAT, WHY, AND HOW? - Chothibul Umam (Al Hikmah: Jurnal Studi Keislaman, 2013)
The best way to improve our knowledge of a foreign language is to go and live among its speakers. The next best way is to read extensively in it (Nuttal, 1982). Current literature points to the importance and benefits of extensive reading. Extensive reading provides contextualized clues for better reading comprehension (Krashen, 1982), and substantial linguistic input (Bell, 1998) needed for language development. Several studies have found a correlation between extensive reading and specific linguistic skills including breadth of reading choices, improved writing skills, ease in oral communication, and improvement in other aspects of language. This paper briefly tries to describe the nature of extensive reading, the reasons why extensive reading is important, and how is the best practice of extensive reading in EFL classroom.